Implementasi Model Problem Based Learning Berbantuan Media PAGER (Papan Geometri) untuk Meningkatkan Penguasaan Konsep Keliling dan Luas Bangun Datar Siswa Sekolah Dasar - Purwanti, Siti; Soebagyo, Joko (Papanda, 2026)
This study aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model assisted by PAGER media (Geometric Board) in improving elementary school students’ mastery of the concepts of perimeter and area of plane figures. The research was conducted with fifth-grade students of SDN Daan Mogot 1, Tangerang City. A quantitative approach was employed using a quasi-experimental design with a one-group pretest–posttest design. The research subjects consisted of 28 students who also served as the research sample. The research instrument was a multiple-choice test that had been validated and tested for reliability, administered before and after the treatment. Data were analyzed using the Shapiro–Wilk normality test, the Wilcoxon signed-rank test, and normalized gain (N-gain) analysis. The normality test results indicated that the data were not normally distributed; therefore, the Wilcoxon test was applied. The Wilcoxon test results showed a Z value of –4.543 with a significance level of 0.000 (< 0.05), indicating a statistically significant difference between pretest and posttest scores. The N-gain value of 71.43% indicates a moderate improvement in students’ conceptual mastery. Based on these findings, it can be concluded that the implementation of the PBL model assisted by PAGER media (Geometric Board) is effective in improving students’ mastery of the concepts of perimeter and area of plane figures at the elementary school level.